Teologia do corpo: alguns princípios éticos a partir da encarnação do Verbo e da prática de Jesus - Oliveira, Marcio Dias de (2014)
This research is based on Theological Anthropology and Sacred Escriture in order to show the incarnation of the Word as a source of ethical principles to the human body. For that took into account the attitudes of Jesus with those wounded in body integrity. The importance of this research is justified due to problems with the body piercing reflected in society through negligence in health, poverty, exploitation and other forms of non recognition of the human being in the physical. The human body is the place of manifestation of God who created it to prove; is the path, through its transcendence for man to go to God who came out to man through human flesh. By a result, the denial of bodily dimension restricts the revelation of God and reduces man to be simple without dignity and transcendence